Case report: Overlapping syndrome mimicking infectious meningoencephalitis in a patient with coexistent MOG, NMDAR, mGluR5 antibody positivity - Fu, Jie; Peng, Lilei; Yang, Yang; Xie, Yang; Li, Zuoxiao; Rong, Benbing (Frontiers in Immunology, 2022)
A 38-year-old Chinese Han man presented with fever, headache and difficulty in language expression. The initial cerebrospinal fluid (CSF) analysis revealed lymphocytic-predominant pleocytosis with a normal glucose level, and magnetic resonance imaging (MRI) showed extensive cortical edema in left cerebral hemisphere. He received the antiviral treatment. However, one week later, he developed psychomotor agitation and seizures. Lumbar puncture was performed again and further testing for autoantibodies was conducted in both the CSF and serum. His CSF was positive for anti-myelin oligodendrocyte glycoprotein (MOG), anti-N-methyl-D-aspartate receptor (NMDAR) and anti-metabotropic glutamate receptor 5 (mGluR5) antibodies. He was diagnosed with overlapping syndrome of MOG antibody-related cerebral cortical encephalitis and anti-NMDAR, anti-mGluR5 autoimmune encephalitis. He received intravenous methylprednisolone and immunoglobulin, followed by oral prednisone and mycophenolate mofetil. His psychomotor agitation and seizures were relieved, and he gradually recovered his language expression ability. We reported for the first time a case that was positive for coexistent MOG, NMDAR, mGluR5 antibodies, which was initially misdiagnosed as infectious meningoencephalitis. This case widens the clinical spectrum of the overlapping syndrome recently reported.